دلالة الأصوات المائعة والصوت المركّب في شعر تأبط شرًّا - حامدي, شوقي; خليفي, عبد الحق (جامعة الوادي - university of Eloued, 2021)
إنّ اللغة بطبيعتهَا تستوجبُ الدراسة العلمية في ذاتها ولذاتها، وفق مستويتها الأربعة، انطلاقا من وحداتهَا الصوْتّية، مُرورًا بالصّرفية، فالتّـركيبية وصولًا إلى الدّلالية، يحاولُ هذا المقالُ إظهار الترابط بين الصوتِ والدّلالة، على مستوى بعض الأصوات، في نُصوصِ شاعرٍ جاهلي مميز، يُعْتبرُ من فئةٍ خاصة في ذلك الزمن؛ هي فئةُ الشعراءِ الصعاليك، وذلك من أجل أنْ نقيسَ مدى تماسكِ بنية هذه النصوص وارتباطها، من خلال الأدوار الدّلالية التي تؤديها الأصوات المائعة والصوت المركب. By its nature, Language requires scientific study in and of itself, according to its four levels, starting with its phonemic units, passing through morphological, structural up to semantic ones. This article attempts to show the correlation between sound and significance at the level of some sounds in the texts of a distinguished pre-Islamic poet, who was considered to be from a special category at that time, the Sa’alik (vagabonds). The purpose is to measure the coherence of the structure of these texts and their relevance, through the semantic roles played by the fluid sounds and the compound sound.
مقال
Keywords: الصوت ; الدّلالة ; الشعر ; الصعاليك ; تأبط شرًّا; sound ; significance ; poetry ; vagabonds ; Ta’abbata Sharran